2008
DOI: 10.1590/s1413-81232008000300029
|View full text |Cite
|
Sign up to set email alerts
|

Saúde e capacidade para o trabalho de eletricitários do Estado de São Paulo

Abstract: The high risks for the health and work ability of the workers of the electricity sector notwithstanding, there is a lack of studies on this topic in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 15 publications
1
14
0
20
Order By: Relevance
“…Decreased WA and poorer health perception occurred among passive workers who did not exercise regularly and reported no leisure activities. Studies conducted in Brazil have also confirmed the association between good health, high WA and good working conditions, both in the administrative sector and among electricians 19,23 .…”
Section: Healthmentioning
confidence: 74%
See 2 more Smart Citations
“…Decreased WA and poorer health perception occurred among passive workers who did not exercise regularly and reported no leisure activities. Studies conducted in Brazil have also confirmed the association between good health, high WA and good working conditions, both in the administrative sector and among electricians 19,23 .…”
Section: Healthmentioning
confidence: 74%
“…Among individual factors, age 13,14 , marital status 15,16 , psychosomatic disorders 17 , self-perception of health 18,19 , depression 9,20 , physical problems 21 and lifestyle habits, such as smoking, drinking and physical activity 22,23 stand out. Work-related predictors include environmental and ergonomic conditions and physical and mental demands 14 .…”
Section: Predictive Factors For Wamentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result was similar to that obtained in a previous study, performed in another population of electrical workers. 17 Length of service in the company was long, showing the stable situation of this population. The fact that some of the workers provided services before being hired or the presence of close relatives in the same organization suggests the existence of a strong relationship between worker and company.…”
Section: Discussionmentioning
confidence: 96%
“…According to the International Labour Organization (ILO) 3 , psychosocial work factors result from the interaction between the work environment (the work organization, conditions and content) and workers' individual conditions (their adaptability, culture, abilities and out-of-work personal needs) which may influence their health status, according to their perception and experiences. Several studies 4,5,6,7,8,9 have reported that psychosocial aspects, such as the effort involved in work activities and the rewards provided by work can influence the mental health status of populations of workers.…”
Section: Introductionmentioning
confidence: 99%